Corneal neovascularization - Nicholas, Matthew P.; Mysore, Naveen (Experimental eye research, 2021)
The optical clarity of the cornea is essential for maintaining good visual acuity. Corneal neovascularization, which is a major cause of vision loss worldwide, leads to corneal opacification and often contributes to a cycle of chronic inflammation. While numerous factors prevent angiogenesis within the cornea, infection, inflammation, hypoxia, trauma, corneal degeneration, and corneal transplantation can all disrupt these homeostatic safeguards to promote neovascularization. Here, we summarize its etiopathogenesis and discuss the molecular biology of angiogenesis within the cornea. We then review the clinical assessment and diagnostic evaluation of corneal neovascularization. Finally, we describe current and emerging therapies. •Summarizes the etiologies and pathogenesis of corneal neovascularization.•Describes the molecular biology of inflammatory corneal neovascularization.•Reviews clinical assessment and diagnostic imaging of corneal neovascularization.•Discusses current and emerging therapies for corneal neovascularization.